POTENSI MICRO-CHINESE MEDICINE OSMOTHERAPY SEBAGAI TERAPI ALTERNATIF PENYAKIT GINJAL KRONIK - Reynaldi Hadiwijaya; Amelia Manatar (DiscoverSys Inc., 2014)
These days, the incidence of chronic kidney disease keep on increasing and the growth is estimated to be 10% annually. According to some data from Indonesia’s nephrology center, the incidence of chronic kidney disease is estimated to be 100-150/1 million population and the prevalence is 250/1 million population. The clinical presentation of chronic kidney disease can be classified into several syndromes. Some are typical for glomerular disease, the other are present in the disease of kidney’s component. In patients with terminal-stage chronic renal failure, Renal Replacement Therapy is required to replace the kidney function. However, Renal Replacement Therapy available now has many drawbacks. Hence, one hospital in China form a team to investigate the effectiveness of the therapy that should be achieved through Micro-Chinese Medicine Osmotherapy. Micro-Chinese Medicine Osmotherapy is a therapy based on the principle of herbs micronisation to cure the disease externally with the help of electronic impulse osmoscope. The drugs can be absorbed directly through the waist to the kidney with the effect of vasodilatation, anti-inflammation, anti-coagulation, regulates the balance of generation and degradation of extracellular matrix and inhibits the process of renal fibrosis